Isolation and Characterization Protease from Black Soldier Fly (Hermetia illucens) - Jaka Satwika Sukma Prana, Made
Black Soldier Fly or Hermetia illucens are insect which coming from tropical regions and areas that have warm temperatures in America. Black Soldier Fly’s life cycle is divided into four phases, egg, larva, pupa, and adult flies phase. Black Soldier Fly has some uniqueness, like having a high protein content of 40-42% and fat of 33-36% and be able to survive with little or even without consuming nutrition. This ability indicate that there are active enzymes in the metabolism of stored food which is reserved in its body. One of the enzyme that are important in providing a source of energy for the flies is protease, a hydrolase enzyme which take part in hydrolyze protein becomes constituent amino acids. In this study, we have been isolated protease from fifty larva and pupa, also twenty five adult flies by homogenization and ammonium sulphate fractination technique. After partial purification, protease in 40- 60% fraction has spesific activity 3.49 U/mg for larva and 3.52 Unit/mg for pupa. In the other hand, adult flies has highest protease’s spesific activity in 60-80% fraction, 9,40 Unit/mg. Proteases from three samples increased their spesific activity after the addition of Mn2+ ion up to 174.24% for larva, 114.18% for pupa dan 214.17% for adult flies. In the state of Mn2+ ion binding, protease’s optimum activity of the three samples are observed at pH 8,0 which has spesific activity 2.99 Unit/mg for larva, 5.75 Unit/mg for pupa, dan 19.73 U/mg for adult flies. These three samples also has same the optimum temperature at 40 ºC, which in the state of Mn2+ ion binding, protease’s spesific activity at this temperature was 2.44 U/mg for larva, 5.75 Unit/mg for pupa and 20.13 U/mg for adult flies. Spesific activity of these three samples decreased after the addition of EDTA becomes 88.42 % for larva, 92.15% for pupa, dan 60.42% for adult flies, indicating that the dependency towards the presence of metal ion was different among those three enzymes. Investigation of the effect of organic solvent as cosolvent revealed that protease’s spesific activity of these three samples has increased after the addition of 1-propanol, 2-propanol, and acetone to the enzyme solution with the volume ratio of 1:1 but decreased butanol and benzene were added. Pupa’s protease demonstrated the longer performance period at the optimum temperature than those of larva’s and adult flies’ proteases. This was due to the different level off the activation energy exhibit during the enzyme’s deactivation process, in which for larva, pupa, and adult flies protease their respective activation energy were 30.478 kJ/mol, 54.899 kJ/mol, and 37.849 kJ/mol. In terms of kinetic’s parameters, larva’s protease has KM 8.551 mg/mL , Vmax 1.976 U/mg ; and kcat 168.127/second; while pupa’s protease has KM = 0,328 mg/mL , Vmax = 3.279 U/mg ; and kcat = 60.736/second. Meanwhile, adult flies’ protease was showing non Michaelis-Menten’s kinetics profile, it tend to follow alosterics kinetics so that it require further analysis in the next study.